The Circulation On The Rio Grande Rise: Mean Flow, Internal Tides, and Eddies - Souza-Neto, Pedro Walfir Martins e (2022)
The Rio Grande Rise (RGR) is an aseismic oceanic elevation with an approximately circular shape in the South Atlantic Ocean, whose center is located at about 31°S and 35°W. The feature extends from 5000 m to approximately 500 m in depth. The RGR is cut from west-east by a fault called Cruzeiro do Sul Rift (CSR). The RGR is an important site for future exploration of Fe-Mn crusts and can lead to an expansion of the Brazil\'s Exclusive Economic Zone. Nevertheless, there is virtually no information about local circulation and its variability. The main objective of this research is to characterize the mean circulation pattern within the CSR, and identify the phenomena associated with its variability. To achieve our objective we use in-situ data, as well as regional numerical modeling, to show that the RGR is a region with several dynamic processes taking place simultaneously. Among them we have the formation of: anticyclonic circulations, internal tides and submesoscale eddies. In general, the southern branch of the South Equatorial Current (SEC) bifurcates around the RGR and is one of the mechanisms responsible for forcing the circulation inside the CSR. Between 500 and 1200 m, around the RGR summits, we observe the formation of asymmetric anticyclonic circulations that play an important role in dictating the circulation inside the CSR. Above the RGR, the internal tides are one of the main mechanisms that generate variability, with wave amplitudes of the same magnitude as the mean flow. Inside the CSR, tides are responsible for generating inversions in the velocity field. Higher tidal amplitudes are located at the RGR summits, with second amplitude peaks adjacent to the bottom at the CSR valley. The amplitude peaks are probably related to the formation of tidal beams due to the steep topography. The circulation within the CSR is dominated by perturbations on impinging SEC branches that often generate submesoscale eddies. Inside the CSR there are three major sites of eddy formation, (1) the east opening (34.5°W), (2) the CSR northern slope opening (35°W) and (3) the west tip of the CSR northern slope opening. In regards to the eddy triggers, the energy conversion analysis indicates the presence of baroclinic and barotropic instability. Also, there is the development of a mix of inertial and symmetric instabilities.